(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: In recent years, dermatological disease patterns in Vietnam, particularly in the Mekong Delta, have undergone complex changes. Multi-dimensional impacts from climate change and rapid lifestyle shifts are driving the demand for high-tech dermatological treatments. Objective: To determine the current status of skin diseases, influencing factors, and the demand for technology application and professional training among physicians in the region in 2025. Research methods: A cross-sectional descriptive study was conducted on 192 physicians working at healthcare facilities in the Mekong Delta. Data were collected via structured questionnaires and analyzed using the Chi-square test (p < 0.05). Results: Acne vulgaris (67.7%), atopic dermatitis (60.9%), and contact dermatitis (60.9%) were the most prevalent conditions. Approximately 79.2% of physicians observed an increasing trend in skin diseases. Primary causes identified included living environment (81.3%), unverified cosmetics (78.1%), and social media information (62.0%). Statistically significant correlations were established between these adverse factors and conditions such as telangiectasia, striae distans, and atopic dermatitis (p < 0.05). Regarding technology, Laser CO2 was the most common (72.9%), while the highest training demands focused on Laser therapy (52.6%) and Platelet-Rich Plasma (PRP) (44.3%). Conclusions: Dermatological disease patterns in the region are escalating due to environmental impacts and maladaptive health behaviors. There is a significant shift from basic procedures toward high-tech laser applications and regenerative medicine. Educational institutions should prioritize continuous medical education (CME) in these fields to meet the practical needs of the regional medical workforce.